TINJAUAN KINERJA PELAYANAN ANGKUTAN UMUM PO KARYA ABADI RUTE BATUSANGKAR-BUKITTINGGI - Ariga, Witari; Bastian, Elfania (Rang Teknik Journal, 2020)
Transportation is an activity that can not be separated from human activities. Especially public transportation as a means of transportation in urban and rural areas. Considering the large demand for demand from the community, limiting human capability makes public transportation the first choice chosen by the community, on the grounds that public transportation is cheaper and more flexible. But the problem that often arises from the transportation sector is the imbalance between demand and supply. Seeing from the importance of public transportation for the activities of all walks of life, in its implementation there needs to be guidance, guidance of the government, so that public transportation can be organized in an orderly, orderly, effective and effective manner from both passengers and operators. The low frequency of vehicles during peak hours and outside peak hours and high waiting times is 5 vehicles / 2 hours during peak hours and 2 vehicles / hours during peak hours. For an average travel speed of 35 km / hour. This speed is influenced by distance, driver's behavior, traffic jams, queue time at traffic light, passengers' ups and downs, the number of disturbances and traffic obstacles during the trip, and the condition of the vehicle itself. Vehicle loading factor is classified as good, namely 61% during peak hours and 23% outside peak hours. Prospective passengers need a waiting time of 30 to get PO Karya Abadi transportation